Nationally competitive scholarships : serving students and the public good : The National Association of Fellowships Advisors 2005 conference proceedings - McCray, Suzanne, 1956- (University of Arkansas Press, 2007)
Guidance for students applying for national scholarships Nationally competitive scholarship programs attract thousands of applicants every year for a relatively small number of awards. Providing informed and dedicated support to applicants is the critical and fundamental goal of the National Association of Fellowships Advisors (NAFA). The thirteen essays in this volume are a direct result of the 2005 NAFA conference held in Louisville. Contributors include both scholarship advisors and representatives of the Truman and Marshall foundations as well as the former executive director of the US-UK.